Spray characteristics of a pintle injector based on annular orifice area. (February 2020) - Lee, Suji; Kim, Daehwan; Koo, Jaye; Yoon, Youngbin
Abstract: As interest in low-cost reusable launch vehicles and extraterrestrial exploration has increased in recent years, soft-landing techniques have become important. A pintle injector can help realize this because it is capable of thrust control. However, research on this topic is very limited, and general optimization design procedures have not been completely established. In particular, no studies have examined orifice adjustment for annular flow, which is important in thrust control. In this study, a new design concept for a pintle injector is presented specifically to improve spray uniformity in a 400 N class engine; this maintains the concentricity of the pintle rod associated with the radial flow's orifice size. The primary focus here was on spray tests that were conducted to obtain the control range of the orifice area for annular flow. Spray characteristics such as spray angle, spray uniformity, and droplet size were analyzed, from which empirical correlations were derived. Finally, the optimum control range for the annular flow's orifice area was estimated from the perspective of atomization performance. This can be of reference to develop an enhanced thrust control system. Highlights: New design concept for a pintle injector was introduced to improve uniformity in a 400 N class liquid rocket engine. Spray tests helped find the control range of the annular flow's orifice area. An appropriate correlation equation was developed for the parameters. The control range was estimated using empirical correlations with respect to the degree of atomization. A database for linear control system design was established.